Phenotypic factors associated with amisulpride‐induced weight gain in first‐episode psychosis patients (from the OPTiMiSE cohort). (19th July 2019) - Pandit, R.; Cianci, D.; ter Hark, S. E.; Winter‐van Rossum, I.; Ebdrup, B. H.; Broberg, B. V.; Garcia‐Portilla, M. P.; Bobes, J.; Vinkers, C. H.; Kahn, R. S.; Guloksuz, S.; Huitema, A. D. R.; et al.
Abstract : Objective: Antipsychotic‐induced weight gain (AiWG) is a debilitating adverse effect of most antipsychotics. First‐episode psychosis patients are particularly vulnerable to the detrimental consequences of AiWG. Amisulpride has good efficacy and tolerability. We here aimed to identify the phenotypic factors associated with amisulpride‐induced weight gain in first‐episode psychosis patients. Method: Data were collected from the Optimization of Treatment and Management of Schizophrenia in Europe trial. Multivariable regression models with various phenotypic variables ( N = 305) were performed with absolute AiWG and clinically relevant AiWG (≥7% AiWG) as outcomes. Results: Four weeks of amisulpride treatment increased body weight from 69.7 to 72.4 kg ( P < 0.001). In the regression model of absolute AiWG, unemployment ( β = 0.94, P = 0.016), younger age ( β = −0.07, P = 0.031) and absence of current comorbid major depression disorder ( β = −1.61, P = 0.034) were positively associated with absolute AiWG. In the regression model of clinically relevant AiWG, unemployment (OR = 2.83, P = 0.001), schizophreniform disorder (OR = 2.00, P = 0.025) and low baseline weight (OR = 0.97, P = 0.032) increased the likelihood of clinically relevant AiWG. Conclusions: Clinicians prescribing amisulpride should consider the relatively high susceptibility to AiWG in unemployed first‐episode patients with psychosis, in particular young subjects with a diagnosis of schizophreniform disorder. We advise to carefully monitor these patients and, when needed, implement weight‐reducing strategies.